EFFECT OF PROTEIN SUPPLEMENTS OF VARYING RUMINAL DEGRADABILITY ON NUTRIENTS INTAKE, DIGESTIBILITY, NITROGEN BALANCE AND BODY CONDITION SCORE IN EARLY LACTATING NILI-RAVI BUFFALOES - Jabbar; M. A; I. B. Marghazani; T. N. Pasha; A. Khalique; M. Abdullah (Journal of Animal and Plant Sciences, 2013)
A study on the effect of protein supplements of varying ruminal degradability on nutrients intake, digestibility, nitrogen balance and body condition score was conducted in early lactating Nili-Ravi buffaloes. Twenty four multi-parous early lactating (22± 10 days) Nili-Ravi buffaloes were selected and randomly divided into four groups (six animals in each group) and fed total mixed rations A, B, C and D containing 30, 40, 50 and 60 % rumen undegradable protein (RUP), respectively in a completely randomized design . Results showed that DM, CP, NDF and ADF intakes were similar (P>0.05) on rations A, B, C and D. DM, CP and NDF digestibility was similar on all rations whilst NDF digestibility was highest (P0.05) by the experimental rations.
Keywords: Protein supplements; rumen degradability; nutrient digestibility; body condition score